SOCIAL WELFARE POLICY AND SOCIO ECONOMIC DEVELOPMENT IN INDONESIA (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. This paper examines the social welfare policy and its contribution to socioeconomic development in Indonesia. This research uses qualitative approach with datacollection technique using literature study. As the results, the government of Indonesiahas implemented several strategies of social welfare policy in order to improve the wellbeingof the citizen, especially the poor people. The main strategy is divided into threeparts, namely social assistance; community empowerment and micro-enterprise program.The implementation of the program has proved that the social welfare programcontributes to the socioeconomic development in Indonesia. However, GoI needs toimprove the program effectiveness. Another matter that we need to consider is thatsocial welfare strategy is not the only approach of reducing poverty. The GoI needs tocombine it with another approach in the socio-economic development context. Socialwelfare policies should be an integrated approach within several policies of employmentand macro-economic strategies in order to reduce risks and increase sustainable growth. Key words: social welfare policy, socio economic development